Human Rights and Migration (Journal of Namibian Studies : History Politics Culture, 2023)
The purpose of this work is to show the relationship that exists between human rights and migration, so that, for the migration process of any person, in the country where he/she is, human rights are respected and guaranteed. It also aims to illustrate the future of migration in the Mexican State when it complies with its human rights obligations.